Rheological improvement in performance of low‐rank coal–water slurries using novel cost‐effective additives. Issue 1 (19th January 2020) - Amin, Naila; Tahir, Muhammad Suleman; Saleem, Mehmood; Khan, Zakir; Aslam, Muhammad; Bazmi, Aqeel Ahmed; Ghauri, Moinuddin; Sagir, Muhammad
Abstract: Coal–water slurry (CWS) has been targeted as a promising fuel and an alternative to fuel oil. CWS has numerous advantages of low and convenient transportation and high solid content. Pakistan is going through a severe energy crisis and among the top 10 countries facing energy crises reported by the United Nations. Besides, Pakistan has become the top seventh country in coal reserves (i.e., 185 billion tones) after the discovery of huge lignite coal reserves in Thar, Sind province. Previous studies investigated the use of additives to enhance CWS properties at a low shear rate and its utilization accordingly. Particularly, the present work studied the high range of shear rate to improve the properties of CWS for transportation and combustion purposes. This study on the improvement in performance of rheology properties of CWS is conducted to improve the properties by cost‐effective additives. The coal concentration varies from 20% to 60%, whereas runs were carried out with and without the cost‐effective additives. The results demonstrated that the coal slurry showed shear‐thinning property when viscosity was increased at high concentrations in the absence of additives. The addition of additive changed the rheological behavior from pseudoplastic to dilatant region. The presence of a high fraction of coal increased the apparent viscosity of CWS. The static stability test of all coal samples was performed using rod drop method at concentrations of 40% to 60%. The study found that stability was achieved earlier with a lower concentration of 40% as compared with higher concentrations of 50–60%. It is expected that this research would be helpful for the country facing adverse energy crises that badly affect the economy and other social aspects of human life.